Părhăuţi-Dealul Muncel, Geomagnetic plan of a Cucuteni-site near Suceava, Romania - Jung, Benedikt; Ignătescu, Sorin; Mischka, Carsten; Mischka, Doris (Arheologia Moldovei, 2024)
https://journals.ub.uni-heidelberg.de/index.php/amold/issue/archi
Keywords: Geomagnetic survey; Cucuteni site; Neolithic; Copper Age; Settlement